PENGARUH KECERDASAN EMOSIONAL DAN EFIKASI DIRI TERHADAP KINERJA KARYAWAN BAGIAN TEKNIK DAN LAYANAN SERVICE PT HASTA PUTERA PERKASA SURABAYA - Maharani Ikaningtyas (Journal Publicuho, 2023)
The purpose of this research was to determine the effect of emotional intelligence and self-efficacy on the performance of employees in the engineering and processing division of PT Hasta Putera Perkasa Surabaya. The research method used is descriptive and associative. The types of data used are primary data and secondary data. Data collection techniques used in this study were interviews, observation, questionnaires, literature study and documentation. Data analysis techniques performed were validity test, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation analysis, analysis of the coefficient of determination, partial hypothesis testing (t test) and simultaneous hypothesis testing (F test). From the results of the analysis of the coefficient of determination, an R2 value of 0.529 is obtained, which means that the influence of emotional intelligence and self-efficacy on employee performance is 52.9%. simultaneously emotional intelligence (X1) and self-efficacy (X2) have a positive and significant effect on employee performance (Y). Meanwhile, based on the t test, the results show that emotional intelligence (X1) has a positive and significant effect on employee performance (Y) and self-efficacy (X2) has a positive and significant effect on employee performance (Y).